Common and Rare Variants in SCN10A Modulate the Risk of Atrial Fibrillation. (February 2015) - Jabbari, Javad; Olesen, Morten S.; Yuan, Lei; Nielsen, Jonas B.; Liang, Bo; Macri, Vincenzo; Christophersen, Ingrid E.; Nielsen, Nikolaj; Sajadieh, Ahmad; Ellinor, Patrick T.; Grunnet, Morten; Haunsø, Stig; et al.
Abstract : Background—: Genome-wide association studies have shown that the common single nucleotide polymorphism rs6800541 located in SCN10A, encoding the voltage-gated Nav 1.8 sodium channel, is associated with PR-interval prolongation and atrial fibrillation (AF). Single nucleotide polymorphism rs6800541 is in high linkage disequilibrium with the nonsynonymous variant in SCN10A, rs6795970 (V1073A, r 2 =0.933). We therefore sought to determine whether common and rare SCN10A variants are associated with early onset AF. Methods and Results—: SCN10A was sequenced in 225 AF patients in whom there was no evidence of other cardiovascular disease or dysfunction (lone AF). In an association study of the rs6795970 single nucleotide polymorphism variant, we included 515 AF patients and 2 control cohorts of 730 individuals free of AF and 6161 randomly sampled individuals. Functional characterization of SCN10A variants was performed by whole-cell patch-clamping. In the lone AF cohort, 9 rare missense variants and 1 splice site donor variant were detected. Interestingly, AF patients were found to have higher G allele frequency of rs6795970, which encodes the alanine variant at position 1073 (described from here on as A1073, odds ratio =1.35 [1.16−1.54]; P =2.3×10 −5 ). Both of the common variants, A1073 and P1092, induced a gain-of-channel function, whereas the rare missense variants, V94G and R1588Q, resulted in a loss-of-channel function. Conclusions—: The common variant A1073 is associated with increased susceptibility to AF. Both rare and common variants have effect on the function of the channel, indicating that these variants influence susceptibility to AF. Hence, our study suggests that SCN10A variations are involved in the genesis of AF. Abstract : Supplemental Digital Content is available in the text.